Machining Performance Of Aluminum Alloy 6061-T6 On Surface Finish Using Minimum Quantity Lubrication - Najiha, M. S.; M. M., Rahman; K., Kadirgama (Universiti Malaysia Pahang, 2015)
This paper presents an experimental investigation of coated carbide cutting tool performance on the surface roughness of aluminum alloy 6061-T6 machining through end mill processes using the minimum quantity lubrication technique. Process parameters including the cutting speed, depth of cut and feed rate are selected. The central composite design method is used for design of experiments. Two types of coated carbide tool are used in this experiment – an uncoated tungsten carbide insert and TiAlN+TiN-coated carbide insert. The analysis of variance method is utilized to validate the experimental data and to check for adequacy. The response surface method was used to develop the mathematical models and to optimize the machining parameters. Second-order regression models are developed based on the surface roughness results. It is observed that the surface roughness depends significantly on depth of cut and feed rate, followed by spindle speed for both the coated carbide inserts. The performance of the dual-layered coating of TiAlN+TiN is competent as compared to the surface quality obtained with TIAlN-coated inserts. The results can be used as an example of MQL applied to the machining of aluminum alloys, providing economic advantages in terms of reduced lubricant costs and better machinability.